Risks in China's financial system - Zheng (Michael) Song; Wei Xiong (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
Motivated by growing concerns about the risks and instability of China's financial system, this article reviews several commonly perceived financial risks and discusses their roots in China's politico-economic institutions. We emphasize the need to evaluate these risks within China's unique economic and financial systems, in which the state and non-state sectors coexist and the financial system serves as a key tool of the government to fund its economic policies. Overall, we argue that: (1) financial crisis is unlikely to happen in the near future, and (2) the ultimate risk lies with China's economic growth, as a vicious circle of distortions in the financial system lowers the efficiency of capital allocation and economic growth and will eventually exacerbate financial risks in the long run.
URN:NBN:fi:bof-201801171100
Keywords: E02; G01; 330